2015
DOI: 10.1007/s00415-015-7678-7
|View full text |Cite
|
Sign up to set email alerts
|

Polyneuritis cranialis: oculopharyngeal subtype of Guillain-Barré syndrome

Abstract: Guillain-Barré syndrome (GBS) constitutes a spectrum of related post-infectious neuropathies, which are characterized by their anatomical patterns of weakness and neurological involvement. Historically, the term polyneuritis cranialis has been used to describe some patients with GBS presenting with multiple cranial neuropathies in the absence of limb weakness. We examine previous reports of polyneuritis cranialis to determine disease characteristics and define new diagnostic criteria. Disease characteristics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
40
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 52 publications
4
40
0
8
Order By: Relevance
“…Although weakness was restricted to facial muscles, limb NCS were abnormal and indicated that subclinical peripheral nerve involvement in BFP can be very diffuse. Similar observations have been noted in a significant proportion of patients with MFS and polyneuritis cranialis despite there being no obvious limb weakness, or in some cases, no loss of tendon stretch reflexes . Interestingly, in our patient, NCS indicated that lower limb nerves were affected more and earlier than upper limb nerves, mirroring that which is typically observed in patients with acute inflammatory demyelinating neuropathy (AIDP) who develop an ascending weakness.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Although weakness was restricted to facial muscles, limb NCS were abnormal and indicated that subclinical peripheral nerve involvement in BFP can be very diffuse. Similar observations have been noted in a significant proportion of patients with MFS and polyneuritis cranialis despite there being no obvious limb weakness, or in some cases, no loss of tendon stretch reflexes . Interestingly, in our patient, NCS indicated that lower limb nerves were affected more and earlier than upper limb nerves, mirroring that which is typically observed in patients with acute inflammatory demyelinating neuropathy (AIDP) who develop an ascending weakness.…”
Section: Discussionsupporting
confidence: 88%
“…Similar observations have been noted in a significant proportion of patients with MFS and polyneuritis cranialis despite there being no obvious limb weakness, or in some cases, no loss of tendon stretch reflexes. 10,16 Interestingly, in our patient, NCS indicated that lower limb nerves were affected more and earlier than upper limb nerves, mirroring that which is typically observed in patients with acute inflammatory demyelinating neuropathy (AIDP) who develop an ascending weakness. Conversely, serial NCS in a patient with pharyngeal-cervical-brachial (PCB) weakness overlap with MFS showed peripheral nerve involvement to be more prominent and develop earlier in the upper limbs, which paralleled the pattern of limb weakness.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…1 In a recent review, we examined the clin ical features of 15 historical cases of poly neuritis cranialis attributed to GBS. 7 In the majority of cases, patients displayed a combi nation of ocular signs (ophthalmo plegia, ptosis or pupillary changes) and bulbar signs (dysarthria or dysphagia), which were often associated with facial weakness. Unlike other GBS subtypes, weakness was frequently asymmetric.…”
mentioning
confidence: 99%